Smart Health Monitoring Systems for Elderly Populations: Opportunities, Challenges, and Global Perspectives - Umar, Fadly; Firmansyah; Ashari, Muhammad Rizki; Syam, Sadli (Medicor : Journal of Health Informatics and Health Policy, 2025)
The global increase in elderly populations has intensified demands for innovative healthcare solutions capable of supporting independence, safety, and chronic disease management. This narrative review explores the role of Smart Health Monitoring Systems (SHMS) in addressing these challenges by synthesizing evidence from diverse medical, engineering, and social science literature. A comprehensive search was conducted in PubMed, Scopus, and IEEE Xplore using keywords such as smart health monitoring, elderly, wearable devices, telemedicine, and assistive technology. Inclusion criteria emphasized studies focusing on SHMS for older adults, with both clinical and technical perspectives considered. The results reveal that wearable devices provide reliable monitoring of falls, vital signs, and daily activity, with reported accuracies exceeding 90%. Integration of IoT and AI technologies further enhances predictive capabilities, enabling early detection of health risks and reducing hospital admissions by as much as 30%. However, adoption remains constrained by systemic barriers, including privacy concerns, fragmented health data, limited digital literacy, and infrastructural deficits in developing regions. The discussion highlights the need for coordinated strategies involving improved digital infrastructure, user education, policy incentives, and interoperability frameworks to overcome these challenges. This review concludes that SHMS represent a transformative innovation for elderly care, but their full potential will only be realized through inclusive design, robust policy support, and culturally sensitive adaptation across diverse healthcare contexts.